Forehead Flap: Master Techniques in Otolaryngology–Head and Neck Surgery - Menick, Frederick J. (Facial Plastic Surgery, 2014)
When the nose is missing, most patients would like to have their normal appearance and function restored. Unfortunately, the wound does not reflect the true tissue loss and the available donor tissues are not similar to nasal tissues. So subunit principles are applied and donor tissues modified to achieve a satisfactory result. All major reconstructions will require a late revision to revise scars, improve asymmetry, or open the airway. However, when cover and lining are grossly deficient, the repair must be totally redone with a second regional flap. Success requires a thoughtful preoperative analysis and careful reconstructive plan. Small nasal defects may be resurfaced in two stages with a forehead flap but large deep defects are best repaired in three stages with an intermediate operation which allows the placement of primary and delayed primary cartilage grafts, soft tissue sculpting, and folded flap lining replacements with safety.
Keywords: nasal reconstruction; forehead flap; lining flap; primary and delayed primary cartilage grafts; revision